Patients’ plasma activity of heparin, low-molecular-weight heparin or no anticoagulants on urine based DOAC test strips - Harenberg, Job; Hetjens, Svetlana; Weiß, Christel (Clinical and applied thrombosis, hemostasis, 2022)
DOAC Dipstick determines specifically the presence and absence of direct oral anticoagulants (DOACs) from patients’ urine samples and handmade test strips performed as well as the commercial version. To compare plasma activity (chromogenic substrate assays) from plasma samples with results from urine samples (DOAC test strips) of patients treated with heparin, low-molecular weight heparin (LMWH) and without anticoagulation. Plasma anti-factor Xa (aXa) activity was determined by Coamatic chromogenic substrate assay and compared to the presence of anticoagulants in urine by DOAC test strips. Patients were treated for least 5 days and samples were taken 4 hrs after administration in comparison to no treatment with an anticoagulant (n = 42). A total of 100 patients were included treated with heparin (n = 29), LMWH nadroparin (n = 29) or no anticoagulants (n = 42). Plasma aXa levels of patients treated with heparin (2 × 7.500 IU daily subcutaneously, 12 male, age 67.4 ± 11.5 years) were 0,18 IU/ml ± 0,15 IU/ml (mean, standard deviation), with LMWH (1 × 3000 IU daily subcutaneously, 15 male, age 64.2 ± 14.1 years) 0,17 IU/ml ± 0,16 IU/l, and with no anticoagulants (28 male, age 64.2 ± 15.6 years) 0,02 IU/ml ± 0.01 IU/ml. All factor Xa and thrombin inhibitor pad results of test strips were negative. We conclude that DOAC Dipstick has a high probability of not detecting heparin and LMWH in patients on treatment as well as in urine samples of patients not treated with an anticoagulant.